Review of Malaysian medicinal plants with potential wound healing activity - Christophe Wiart; Tan, Puay Luan; Mogana Rajagopal; Chew, Yik-Ling; Leong, Mun Yee; Tan, Lee Fang; Yap, Vi Lien (BioMed Central Ltd., 2024)
Wound is defined as the damage to biological tissues including skin, mucous membranes and organ tissues. The acute wound heals in less than 4 weeks without complications, while a chronic wound takes longer than 6 weeks to heal. Wound healing occurs in 4 phases, namely, coagulation, inflammatory, proliferative and remodeling phases. Triclosan and benzalkonium chloride are commonly used as skin disinfectants in wound healing. However, they cause allergic contact dermatitis and antibiotic resistance. Medicinal plants are widely studied due to the limited availability of wound healing agents. The present review included six commonly available medicinal plants in Malaysia such as Aloe barbadensis Miller, Carica papaya Linn., Centella asiatica Linn., Cymbopogon nardus Linn., Ficus benghalensis Linn. and Hibiscus rosa sinensis Linn. Various search engines and databases were used to obtain the scientific findings, including Google Scholar, ScienceDirect, PubMed Central and Research Gate. The review discussed the possible mechanism of action of medicinal plants and their active constituents in the wound healing process. In addition, their application in nanotechnology and wound dressings was also discussed in detail.